Effect of nano-silica on structure and properties of high sulfate resistant Portland cement mixed with mineral powder or fly ash. (1st May 2023) - Dai, Jing; Gong, Chenchen; Wang, Yanfei; Huo, Liuqing; Lu, Lingchao
Abstract: Hydrating-hardening properties of high sulfate resistance Portland cement (HSRPC) mixed with 35 wt% mineral powder (MP) or fly ash (FA) and the action mechanism of nano-silica (NS) under the condition of low-calcium hydrating phase were studied in this paper. Rheology, fluidity, setting time and compressive strength were investigated to explore the effect of NS on the basic physical properties of HSRPC doped with MP or FA. Mercury intrusion porosimetry (MIP), ultrasonic crack analysis, hydration heat and thermogravimetry (TG) were investigated to analyze the hardened structure and the hydration mechanism. The conclusions were as follows: For HSRPC with MP, the 0.1–0.5 wt% NS increased the yield stress, decreased the fluidity and prolonged the setting time. However, when NS content increased from 0.1 wt% to 0.5 wt%, the cumulative porosity increased by 9.8% and the 60 h (60 h) cumulative hydration heat decreased by 14.6% because NS with high specific surface area inhibited the hydration of HSRPC, but its particle filling increased the porosity of harmless pores to improve the 3day (3d) compressive strength slightly. After 28d of hydration, the compressive strength increased by 2.8%, ultrasonic amplitude increased by 19.3%, and calcium hydroxide (CH) decreased by 6.6%, indicating that NS fully reacted with CH generated by HSRPC hydration. For HSRPC with FA, the 0.1–0.3 wt% NS increased the yield stress, setting time and 3d compressive strength and decreased the cumulative porosity. The 60 h cumulative hydration heat increased from 155.9 J/g to 198.5 J/g. The ultrasonic amplitude of 28d hardened paste increased from 10.91 V to 17.01 V and the CH content decreased from 15.29% to 14.1%. It indicated that the 0.1–0.3 wt% NS with high activity reacted with CH and further promote cement hydration to generate a large number of hydration products to improve the densification and performance, especially at the early age. Highlights: The NS effectively played the role of high activity and particle filling during low-calcium HSRPC. The porosity of harmless pores of 3d hardened HSRPC paste with MP increased by 10.7% when NS content was increased from 0.1 wt% to 0.5 wt%. The 0.1–0.3 wt% NS increased the 28d compressive strength of HSRPC with FA by 4.5–19.5%.